Role of preoperative carbohydrate loading in reducing port site pain following laparoscopic cholecystectomy for gall stone disease - Hasan, M. Mahmudul; Rahat, S. M. Asikur; Siddique, M. Ibrahim; Chowdhury, Rajib; Alrazy, M. Alim; Mazumdar, Rokebul H.; Akter, Nayeemun; Tanha, Fahmida S.; Uddin, M. Nadim (International Surgery Journal, 2025)
Background: Laparoscopic cholecystectomy is the gold standard for gallstone disease, though postoperative port-site pain remains common. Preoperative carbohydrate loading, an enhanced recovery after surgery (ERAS) component, helps reduce fasting discomfort and enhance recovery. This study aimed to assess its role in reducing port-site pain and analgesic use after laparoscopic cholecystectomy. The aim of the study was to evaluate the effect of preoperative carbohydrate loading on postoperative port site pain in patients undergoing laparoscopic cholecystectomy for gallstone disease. Methods: This prospective observational study was conducted at the Department of General Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka, from February 2023 to January 2024. Sixty cholelithiasis patients were assigned to a control group (fasting) or an intervention group (preoperative carbohydrate drink). Postoperative pain (VAS), analgesic timing, and total doses were recorded. Data were collected via a predesigned questionnaire and analyzed using statistical package for the social sciences (SPSS) 22.0. Results: In 60 patients, baseline characteristics were comparable (p>0.05). Postoperative pain scores were lower in the intervention group at 6 hours (4.53 versus 5.13), 12 hours (4.93 versus 5.40), 18 hours (3.92 versus 4.31), and 24 hours (2.82 versus 3.27) (p<0.05). Time to first and repeat analgesic doses was longer (7.20 versus 6.73 hours; 15.40 versus 14.90 hours; p<0.05), and total analgesic dose was lower (2.80 versus 3.53; p=0.001) compared to controls. Conclusions: Preoperative carbohydrate loading significantly reduced postoperative pain and the total analgesic requirement, with the intervention group needing fewer doses than the control group.